Voltmeter Design Based on ADS1115 and Arduino Uno for DC Resistivity Measurement - Risky Martin Antosia (JTERA (Jurnal Teknologi Rekayasa), 2020)
One part of the geoelectric method is DC (Direct Current) resistivity measurement. Physical parameters measured by the system are the current and potential difference. From these two parameters, the resistance value is obtained based on Ohm’s law. Based on the current-potential electrodes configuration in the DC resistivity measurement, there is the possibility of contact between the potential-current electrodes and also the position of the potential electrodes that can be exchanged. Thus, an auto-range Voltmeter is needed which can measure the potential difference with the order of mV up to hundreds of volts and can measure negative potential difference value (reversed polarity). This research aims to build a Voltmeter prototype using ADS1115 (namely ADC with 16-bit resolution) and Arduino Uno, which can be applied in DC resistivity measurement. In this system, there is internal resistance and switch. The internal resistance is around 2.4 MΩ, arranged into a voltage divider circuit to be able to measure the maximum potential input around 1,600 V. The switch function is to set the measurement mode (as auto-range), which is set by Arduino Uno. Furthermore, ADS1115 uses a differential measurement method to be able to measure a negative potential difference. Based on the results of tests on several resistor components with an adjustable voltage source, the Voltmeter is good at measuring the potential difference in resistor values below 10 KΩ with a confidence level of around 97%.